The importance of visual field testing in patients with papilledema and idiopathic intracranial hypertension - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Aim : To determine the role of visual field testing in the monitoring of patients with idiopathic intracranial hypertension. Material and methods : 48 patients with newly diagnosed idiopathic intracranial hypertension were enrolled. Routine neurologic and ophthalmic examinations as well as automated perimetry were performed in all patients at baseline and 4–6 months later. Based on baseline findings, the subjects were referred for further treatment which included reduction of body weight, sodium-restricted diet, oral acetazolamide or other diuretic agent, corticosteroids and, in three cases, also optic nerve sheath decompression. Results : 39 patients (81%) presented with visual field defects on baseline perimetry. The most commonly found visual field defects included blind spot enlargement, usually with concomitant partial peripheral rim (29 eyes, 38.7%), generalized constriction (16 eyes, 21.3%) and nerve fiber bundle defect with or without concomitant blind spot enlargement (15 eyes, 20%). In 28 patients (58%), the findings of follow-up perimetry differed from baseline. Visual field defects were found in 3 persons with normal visual field at baseline. Up 60% of treated patients with abnormal baseline perimetry showed an improvement in visual field parameters, whereas 86% of untreated patients had no change in visual field parameters whatsoever. Conclusions : Treatment of patients with idiopathic intracranial hypertension contributes to the improvement of visual field parameters. Ophthalmic examination with perimetry is a critical component of baseline status evaluation, treatment recommendations and monitoring treatment outcomes in patients with idiopathic intracranial hypertension.